Psoriatic arthritis due to nivolumab administration a case report and review of the literature. (2018) - Sapalidis, Konstantinos; Kosmidis, Christoforos; Michalopoulos, Nikolaos; Koulouris, Charilaos; Mantalobas, Stylianos; Giannakidis, Dimitrios; Munteanu, Alexandru; Surlin, Valeriu; Laskou, Stella; Zarogoulidis, Paul; Drougas, Dimitrios; Sardeli, Crysanthi; et al.
Abstract: Nowadays we have novel equipment for lung cancer diagnosis, however; due to lack of symptoms, lung cancer is still diagnosed at a late stage. Currently we have the following therapies for non-small cell lung cancer: a) non-specific cytotoxic agents, b) targeted therapies and c) immunotherapy. Each therapy has its own advantages and adverse effects. In the current case we will present a rare case of psoriacic arthritis that was presented after two cycles of nivolumab administration and we will also present a review of the literature.